Aplikasi Pelayanan Asisten Tutor Berbasis Android di Universitas Kristen Petra - Dieni Lucky Prayapitesha; Andreas Handojo; Anita Nathania (Jurnal Infra, 2020)
Ethics Enrichment is a coaching program for new students during the first semester. This development program will divide new students into several small groups which led by Asisten Tutor (Astor). Besides making a development program, Asisten Tutor (Astor) must join another development program like intensive fellowship and Bible study groups. Each group has a mentor in order to lead the group. At this moment, every equippment that is used for new students, Asisten Tutor (Astor), and mentor is still printed in papers. With the numbers of new students, Asisten Tutor (Astor), and mentor that are increasingly rise every year; the usage of papers is such a waste and it is not simple. Therefore, web application dan mobile application are exist in order to help Asisten Tutor (Astor) and mentor; and also help new students to follow this development program effectively. This application is a technology-based because the usage of technology is a need for everyone in this era. The users of web application consist of administrator, asisten tutor observer, and students observer. Thus, the users of mobile application consist of mentor, Asisten Tutor (Astor), and new students. According to the test result, web application and mobile application is accesible. This application also helps management system of Ethics Enrichment service become well-organized.